Determinants of Workplace Stress with an Emphasis on Technology - Pranjal Seth (International Journal of Advanced Science and Technology, 2020)
Occupational stress is one of the main factors that can make or break a successful career. With increasing workloads and competitiveness, the stress level in organisations is rising. However, the revolutionary changes being brought about in organisations over the past decade or two has been the increasing integration of technology in the workplace. This paper will first attempt to define occupational stress briefly to set the context of the research. Subsequently it will attempt to detail the aspects of the impact technology is having on occupational stress. One of these aspects is the insurgence of artificial intelligence which is significantly changing job roles as well as the competencies and skills required to perform the same. Learning agility has become of much more importance and there is increasing uncertainty about the relevance of the current skills and which will be the skills required in future. The second aspect is in finding out whether the new methods of work emerging through integration with technology have increased or decreased workplace stress. The study will also find differences in the impact had across age groups and sectors depending on the use of technologies like information systems, cloud-based platforms etc. Other determinants of work stress will also be touched upon. Primary surveys will be conducted to determine the validity of the hypotheses and subsequently the results analysed through statistical tools.